2017
DOI: 10.1088/1555-6611/aa6587
|View full text |Cite
|
Sign up to set email alerts
|

Switchable multiwavelength ytterbium-doped fiber laser using a non-adiabatic microfiber interferometer

Abstract: In this paper, we have successfully demonstrated a stable dual, triple and quad-wavelength generation of ytterbium-doped fiber by incorporating a non-adiabatic microfiber interferometer (N-MI) into the laser ring cavity. Three sets of dual-wavelength, two sets of triple-wavelength and one set of quad-wavelength with the same wavelength spacing of 4.24 nm for all sets of multiwavelengths over the range of 1035 nm to 1050 nm are obtained by means of a nonlinear polarization rotation mechanism. The side-mode supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 24 publications
(28 reference statements)
0
11
0
Order By: Relevance
“…We can understand this character as follows: In a single-mode tapered fiber, when the fundamental mode propagated from the untapered region to the tapered region, higher-order modes would be excited in the tapered region, then the fundamental modes and higher order modes would be coupled together in the untapered region, and interference effect was formed. So the tapered fiber can be used as a filter to generate stable multiple wavelengths [40]- [42]. Further study showed that the free spectral range (FSR) can be expressed as [43], [44]:…”
Section: Discussionmentioning
confidence: 99%
“…We can understand this character as follows: In a single-mode tapered fiber, when the fundamental mode propagated from the untapered region to the tapered region, higher-order modes would be excited in the tapered region, then the fundamental modes and higher order modes would be coupled together in the untapered region, and interference effect was formed. So the tapered fiber can be used as a filter to generate stable multiple wavelengths [40]- [42]. Further study showed that the free spectral range (FSR) can be expressed as [43], [44]:…”
Section: Discussionmentioning
confidence: 99%
“…All-fiber polarization interference filter based uniform multiwavelength erbium-doped fiber laser interferometer [30,31], chirped or sampled fiber grating [32] and a microfiber interferometer [33]. In recent years, the Lyot filter has attracted considerable interest for generating multiwavlength fiber lasers due to its all fiber structure and convenience in choosing wavelength spacing [20,21,34,35].…”
Section: Laser Physicsmentioning
confidence: 99%
“…In [52], an Yb-doped MZI used as WSF, resulted in a laser with a SMSR of 40 dB, a linewidth of 0.07nm, and stability of 1 dB during 30 minutes of testing. In [53] a non-adiabatic microfiber Mach-Zehnder interferometer was used as a WSF, obtaining a laser with a SMSR of 53 dB, a linewidth of 0.01 nm, and stability 0.6 dB during 20 minutes of testing. Recently, in [48], the switchable emission was controlled by bending a bitaper MZI, obtaining a SMSR of about 32 dB.…”
Section: Introductionmentioning
confidence: 99%